ELEMENTARY SCHOOL TEACHER’S OBSTACLES IN THE IMPLEMENTATION OF PROBLEM-BASED LEARNING MODEL IN MATHEMATICS LEARNING - Nurlaily, Vivi Astuti; Soegiyanto, Heribertus; Usodo, Budi (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2019)
This study aims to describe the teachers' obstacles in applying problem-based learning model in Mathematics learning of elementary schools. This method of this study was a qualitative descriptive. The data sources were three third-grade teachers of the elementary schools. The data analysis consisted of stages of data collection, data reduction, data presentation, and data verification. The results of the study show: in the planning stage, obstacles occur when teachers need careful preparation in making learning plans and determining problems at the beginning of learning. In the implementation phase, the obstacle that occurs is a lack of time in maximizing activities in all phases. The teacher finds it difficult to direct students to problems that require solutions. Teachers need enough time to organize students in group activities. Also, they have difficulty dividing time when guiding groups because students are still waiting for the teacher to explain to the group without doing it themselves first. Another difficulty faced is making students actively ask questions or respond to learning activities, and feedback from problem-solving is less profound.